Preparation method of MXene / lignin two-dimensional nanosheet composite material and application of MXene / lignin two-dimensional nanosheet composite material in ultraviolet shielding

The preparation of MXene/lignin composite materials by mechanochemical method solves the problem of easy agglomeration and poor resistance to UV inorganic anti-UV materials, and achieves efficient ultraviolet shielding and anti-oxidation effects.

CN119679638APending Publication Date: 2025-03-25JIANGSU NAO NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411911147.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing inorganic anti-ultraviolet materials are prone to agglomeration and have poor UV resistance. At the same time, organic materials are harmful to the human body and the environment.

Method used

Mechanochemical method was used to prepare the MXene/lignin two-dimensional nanosheet composite material, and the MXene structure was looser by ball milling. The lignin nanosheets were intercalated in the MXene sheet structure, preventing the aggregation and stacking of MXene nanosheets.

Benefits of technology

It effectively avoids the agglomeration phenomenon of MXene, increases the layer spacing, significantly improves the ultraviolet shielding ability of the composite material, and fully utilizes the material's own antioxidant ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of ultraviolet shielding materials, in particular to a preparation method of an MXene / lignin two-dimensional nanosheet composite material and application of the MXene / lignin two-dimensional nanosheet composite material in ultraviolet shielding. The preparation method comprises the following steps: performing vacuum freeze drying on a lignin deionized water dispersion liquid to obtain flake lignin, dissolving Ti3AlC2MAX powder into a lithium fluoride and concentrated hydrochloric acid solution to obtain etched MXene, dispersing the etched MXene and the flake lignin into an ammonia water solution, mixing, and performing ball milling to obtain a modified MXene solution; and separating solids from the obtained suspension, washing to be neutral, and freeze-drying to obtain the MXene / lignin composite nanosheet composite material. The lignin nanosheets are intercalated in the lamellar structure of MXene, on one hand, the agglomeration phenomenon among the lignin nanosheets is avoided, and on the other hand, the phenomenon that part of MXene is not stripped and layered is solved, so that the MXene forms a uniform nanosheet structure, and the whole MXene shows good ultraviolet shielding capability and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultraviolet shielding materials, and in particular to a preparation method and application of a MXene / lignin two-dimensional nanosheet composite material. Background Art

[0002] In recent years, the incidence of skin cancer has been rising due to the fact that ultraviolet radiation from the sun can cause serious damage, including sunburn, photoaging, oxidative stress and carcinogenesis. Based on this, sunscreens are used to protect people from the harm of ultraviolet rays, and the sunscreen components are divided into organic sunscreens and inorganic sunscreens. Organic UV filters have a higher risk of allergies and dermatitis. At the same time, people have found that organic UV filters are present in almost all water sources around the world. Inorganic UV filters have the advantages of photostability, non-irritation, broad-spectrum protection and cost-effectiveness. However, these nanoparticles tend to form aggregates and agglomerates when suspended, affecting their UV protection and transparency. Therefore, combining inorganic ingredients with natural organic ingredients in sunscreens has become an emerging research direction in the field of UV protection.

[0003] MXene is a two-dimensional material composed of layered ceramic precursors, usually Mn +1 AX n (MAX) phase materials are synthesized by selectively etching A elements (Al, Si or Ga). It is reported that Ti3C2T x MXene has a narrow band gap (0.92–1.75 eV) and exhibits efficient UV absorption. At the same time, MXene has a physical barrier effect due to its unique lamellar morphology and can reflect a certain amount of UV light. The TiC contained in the successfully etched MXene will oxidize to TiO2 under certain conditions, which has a certain UV resistance effect. At the same time, the processed MXene has a nanosheet structure, but it is prone to agglomeration.

[0004] As one of the abundant natural renewable polymers, lignin is green and non-toxic, and is a renewable green resource. Lignin is a complex aromatic polymer compound, which is polymerized by three main alcohol monomers (p-coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol). It has abundant active groups such as phenolic hydroxyl groups and has strong biological activity. Studies have shown that lignin has structures such as phenolic hydroxyl groups, carbonyl groups, and conjugated double bonds as chromophores. These structural properties enable it to absorb wide-spectrum ultraviolet radiation in the range of 250-400 nm, giving it excellent ultraviolet absorption capacity. At the same time, lignin also has antioxidant activity, and its antioxidant properties are mainly related to the phenolic hydroxyl content in its molecular structure. Methoxy groups and purity also affect its antioxidant properties. Based on this, lignin has been developed as a natural UV blocker and has been shown to have long-lasting protective ability. Lignin is ultrasonically layered to form a nanosheet structure with good anti-ultraviolet and antioxidant properties.

[0005] Chinese patent CN108420751A mixes bamboo powder with tetrahydrofuran, puts the solution into a dialysis bag for 24h, and freeze-dries to obtain lignin nanoparticles. Toxic organic solvents are used in the preparation process. Chinese patent CN112072085A dissolves lignin in an alkaline solution for hydrothermal pretreatment, adjusts its pH to 3-5 at room temperature, dissolves soluble zinc salts and soluble carbonates in water, and then adds them to the acid-soluble lignin solution for hydrothermal reaction to obtain a lignin / zinc oxide complex solution. Aldehydes are added to the lignin / zinc oxide complex solution for hydrothermal reaction. After cooling to room temperature, the precipitate is filtered and separated, washed, and dried to obtain a polycondensed lignin / zinc oxide complex. CN202411054398.7 A preparation method and application of a layered hydroxide / de-alkali lignin composite material. The inventor previously used dealkalized lignin and zinc-titanium layered hydroxide, which was applied in a sunscreen vaseline matrix to exert a UV shielding effect. However, compared with zinc-titanium layered hydroxide, MXene is less stable and prone to agglomeration, making it difficult to prepare MXene-related UV shielding materials. MXene is a very good UV shielding material, but there is currently little research on the application of MXene in UV shielding materials. Based on this, there has been no report on combining the inorganic component MXene with the natural organic component lignin for anti-UV materials. Summary of the invention

[0006] In order to solve the harm of organic anti-ultraviolet materials to human body and environment and the problem that inorganic anti-ultraviolet materials are easy to agglomerate and have poor anti-ultraviolet ability, the present invention proposes a method for preparing a MXene / lignin two-dimensional nanosheet composite material.

[0007] In order to achieve the purpose of the present invention, the following technical solutions are adopted: (1) An appropriate amount of lignin and deionized water were ultrasonically dispersed (solid-to-liquid ratio of 1:20-40), ultrasonicated at 225-250 W for 20-30 min, and freeze-dried in a vacuum at -35-55 °C to obtain flaky lignin.

[0008] (2) Dissolve an appropriate amount of lithium fluoride in a 9-10M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.02-0.08 g / mL, and then gradually add an appropriate amount of Ti3AlC2MAX powder to the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX is 1-5:1, and react at 25-50°C for 24-48 hours; centrifuge at a speed of 8000-10000 rpm for 3-9 minutes, wash with deionized water to pH = 7, and freeze-dry the resultant to obtain MXene.

[0009] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) are added to an ammonia solution with a concentration of 0.52 M to 3.72 M in a mass ratio of 1:0.5 to 2 to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.045 g / mL to 0.27 g / mL, and the mixture is stirred at room temperature for 0.5 to 1.5 h. The mixture is ball-milled in a ball mill at a speed of 450 to 600 rpm for 3 to 6 h using a mechanochemical method to obtain a MXene / lignin nanosheet mixed solution. The precipitate obtained after centrifugation is freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0010] The present invention makes the structure of MXene looser through ball milling treatment. At the same time, the rich oxygen-containing groups on the surface of lignin give it excellent hydrophilicity and chemical reactivity, so that it can interact well with the −OH and −F groups on the surface of MXene, and then interact with MXene, and insert well between the sheets of MXene, preventing the aggregation and stacking of MXene nanosheets, and effectively increasing the interlayer spacing of MXene. Inserting lignin nanosheets into the sheet structure of MXene avoids the agglomeration phenomenon between lignin nanosheets on the one hand, and the dispersed nano-sized lignin sheets have excellent ultraviolet absorption capacity. The synergistic effect of lignin and MXene significantly improves the ultraviolet shielding ability of the composite material.

[0011] The MXene / lignin nanosheet composite material prepared by the method of the present invention has a higher specific surface area, avoids agglomeration, and gives full play to the anti-ultraviolet and anti-oxidation capabilities of the material itself.

[0012] Compared with the prior art, the advantages of the present invention are: 1. The mechanochemical method promotes the exfoliation and intercalation of lignin to MXene. The introduction of lignin increases the active adsorption sites, improves the shortcomings of MXene nanosheet aggregation and stacking, increases the interlayer spacing, and enhances stability.

[0013] 2. Part of the Ti in MXene is oxidized to TiO2 over time, continuously improving the UV resistance of the composite material. The lignin inserted between the layers has good dispersion and excellent antioxidant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 XRD spectrum of the MXene sample prepared in Example 1; Figure 2 TEM images of the MXene / lignin flake structure c) prepared in Example 1, the MXene flake structure b) after etching, and the lignin flake structure a) sample with a scale range of 50 nm, 0.2 µm, and 100 nm; Figure 3 The SPF values ​​of Examples 1 to 5 and their comparative examples, flaky lignin, and etched flaky MXene are compared and summarized. DETAILED DESCRIPTION

[0015] Embodiment 1:

[0016] (1) 0.5 g of lignin was dispersed with 20 ml of deionized water by ultrasonication (solid-liquid mass ratio was 1:40), ultrasonicated at 225 W for 20 min, and freeze-dried in a vacuum at -35 °C to obtain flaky lignin.

[0017] (2) Dissolve 1 g of lithium fluoride in 9 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.05 g / mL, and then gradually add 1 g of Ti3AlC2MAX powder into the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX is 1:1. After reacting at 25°C for 24 h; centrifuge at 8000 rpm for 4 min, wash with deionized water to pH = 7, and freeze-dry the resultant.

[0018] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 0.52 M ammonia solution at a mass ratio of 1:1 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.095 g / mL. The mixture was stirred at room temperature for 0.5 h. The mixture was subjected to a mechanochemical method and ball milled at 450 rpm for 3 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0019] An X-ray powder diffraction experiment was performed on the MXene / lignin composite material prepared in this example, its morphology and structure were observed under a transmission electron microscope, and its ultraviolet shielding effect was tested under an SPF instrument.

[0020] XRD spectrum Figure 1 As shown: MXene material shows multiple diffraction peaks, which are MXene diffraction peaks; in addition, the TEM photo of MXene / lignin sample is as follows Figure 2 a)- Figure 2 As shown in Figure c), the prepared MXene and lignin are stacked in a sheet-by-sheet manner, providing a larger interface area, reducing agglomeration, and improving UV shielding ability.

[0021] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, according to the Colipa standard, 100 mg of powder and 900 mg of glycerin were mixed evenly in an agate mortar to prepare a simulated sunscreen with a mass ratio of 1:9. 32.5 mg of the sample to be tested was weighed on a PMMA test plate (5×5 cm) using an analytical balance, and evenly applied with a finger wearing a cot, and the sun protection index of the sample was tested using an SPF meter. The higher the sun protection index, the better the ultraviolet shielding ability, and the value in this embodiment is 10.2. Embodiment 2:

[0022] (1) 1 g of lignin was dispersed with 30 ml of deionized water by ultrasonication (mass ratio of 1:30), ultrasonicated at 225 W for 30 min, and freeze-dried in a vacuum at -35 °C to obtain flaky lignin.

[0023] (2) 4 g of lithium fluoride was dissolved in 9 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.06 g / mL, and then 1 g of Ti3AlC2MAX powder was gradually added to the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX was 4:1. After reacting at 45°C for 36 h; centrifuged at 9000 rpm for 4 min, washed with deionized water to pH = 7, and freeze-dried.

[0024] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 1.19 M ammonia solution at a mass ratio of 1:1.5 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.093 g / mL. The mixture was stirred at room temperature for 1 h. The mixture was subjected to a mechanochemical method and ball milled at 450 rpm for 4 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0025] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, the value of this embodiment is 10.6. Embodiment 3:

[0026] (1) 1 g of lignin was dispersed with 20 ml of deionized water by ultrasonication (mass ratio of 1:20), ultrasonicated at 250 W for 20 min, and freeze-dried in a vacuum at -45 °C to obtain flaky lignin.

[0027] (2) Dissolve 3 g of lithium fluoride in 10 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.02 g / mL, and then gradually add 1 g of Ti3AlC2MAX powder into the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX is 3:1. After reacting at 25°C for 24 h; centrifuge at 10000 rpm for 3 min, wash with deionized water to pH = 7, and freeze-dry the resultant.

[0028] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 3.72 M ammonia solution at a mass ratio of 2:1 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.27 g / mL. The mixture was stirred at room temperature for 1 h. The mixture was subjected to a mechanochemical method and ball milled at 500 rpm for 3 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0029] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, the value of this embodiment is 10.7. Embodiment 4:

[0030] (1) 0.5 g of lignin was dispersed with 20 ml of deionized water by ultrasonication (mass ratio of 1:40), ultrasonicated at 225 W for 20 min, and freeze-dried in a vacuum at -35 °C to obtain flaky lignin.

[0031] (2) Dissolve 5 g of lithium fluoride in 10 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.06 g / mL, and then gradually add 1 g of Ti3AlC2MAX powder into the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX is 5:1. After reacting at 45°C for 36 h; centrifuge at 9000 rpm for 4 min, wash with deionized water to pH = 7, and freeze-dry the resulting product.

[0032] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 1.46 M ammonia solution in a mass ratio of 1:2 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.045 g / mL. The mixture was stirred at room temperature for 1.5 h. The mixture was subjected to a mechanochemical method and ball milled at 600 rpm for 5 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0033] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, the value of this embodiment is 10.5. Embodiment 5:

[0034] (1) 2 g of lignin was dispersed with 40 ml of deionized water by ultrasonication (mass ratio of 1:20), ultrasonicated at 250 W for 30 min, and freeze-dried in a vacuum at -55 °C to obtain flaky lignin.

[0035] (2) Dissolve 2 g of lithium fluoride in 9 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.08 g / mL, and then gradually add 1 g of Ti3AlC2MAX powder into the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2MAX is 2:1. After reacting at 50°C for 48 h; centrifuge at 9000 rpm for 9 min, wash with deionized water to pH = 7, and freeze-dry the resultant.

[0036] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 0.89 M ammonia solution in a mass ratio of 1:2 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.013 g / mL. The mixture was stirred at room temperature for 1.5 h. The mixture was subjected to a mechanochemical method and ball milled at 550 rpm for 6 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0037] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, the value of this embodiment is 10.5. Comparative Example 1:

[0038] (1) 0.5 g of lignin was dispersed with 20 ml of deionized water by ultrasonication (solid-liquid mass ratio was 1:40), ultrasonicated at 225 W for 20 min, and freeze-dried in a vacuum at -35 °C to obtain flaky lignin.

[0039] (2) Dissolve 1 g of lithium fluoride in 9 M concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution with a concentration of 0.05 g / mL, and then gradually add 6 g of Ti3AlC2 MAX powder into the mixed solution, wherein the mass ratio of lithium fluoride to Ti3AlC2 MAX is 1:6. After reacting at 25°C for 24 h; centrifuge at 8000 rpm for 4 min, wash with deionized water to pH = 7, and freeze-dry the resulting product.

[0040] (3) The flaky lignin obtained in step (1) and the MXene obtained in step (2) were added to a 0.52 M ammonia solution at a mass ratio of 1:1 and mixed to obtain a MXene / lignin ammonia mixed solution with a concentration of 0.095 g / mL. The mixture was stirred at room temperature for 0.5 h. The mixture was subjected to a mechanochemical method and ball milled at 450 rpm for 3 h to obtain a uniformly distributed MXene / lignin nanosheet mixed solution. The mixture was centrifuged and freeze-dried to obtain a MXene / lignin composite nanosheet structure.

[0041] The SPF value spectrum of MXene / lignin composites is shown in Figure 3 As shown, the value of this embodiment is 2.9. The MXene prepared in this comparative example is not etched with excessive lithium fluoride, so that the MXene cannot form a dispersed sheet structure, the MXene agglomerates, and the ultraviolet shielding ability is weak. Comparative Example 2:

[0042] Comparative Example 2 is compared with Example 3, except that the mass ratio of flaky lignin to MXene is 1:10, and other operations are the same as Example 3.

[0043] The SPF value spectrum of the MXene / lignin composite material prepared in Comparative Example 2 is as follows: Figure 3 As shown, the value of this embodiment is 3.3.

[0044] The mass ratio of MXene to lignin in the composite material prepared in this comparative example is not appropriate, and a small amount of lignin is lost after ball milling and cannot form a composite structure with a large amount of MXene. MXene agglomerates and has a weak UV shielding ability. Comparative Example 3:

[0045] Comparative Example 3 is compared with Example 3, except that the mass ratio of flaky lignin to MXene is 10:1, and other operations are the same as Example 3.

[0046] The SPF value spectrum of the MXene / lignin composite material prepared in Comparative Example 3 is as follows: Figure 3 As shown, the value of this embodiment is 3.1.

[0047] The mass ratio of MXene to lignin in the composite material prepared in this comparative example is not appropriate. A small amount of MXene is converted into a smaller nanosize after ball milling, and some larger-sized lignin cannot form a composite structure with MXene, and the ultraviolet shielding ability is weak. Comparative Example 4:

[0048] The difference between Comparative Example 4 and Example 3 is that the concentration of the ammonia solution in step (3) is 5.2 M, and the other operations are the same as those in Example 3.

[0049] The SPF value spectrum of the MXene / lignin composite material prepared in Comparative Example 4 is as follows: Figure 3 As shown, the value of this embodiment is 3.5.

[0050] The composite material prepared in this comparative example was treated with a large amount of ammonia water, and the strong alkali destroyed the structure of a part of the lignin, making the ultraviolet shielding ability of the MXene / lignin nanosheets weaker. Comparative Example 5:

[0051] Compared with Example 3, Comparative Example 5 differs in that the ammonia water in step (3) is replaced by deionized water, and the other operations are the same as those in Example 3.

[0052] The SPF value spectrum of the MXene / lignin composite material prepared in Comparative Example 5 is as follows: Figure 3 As shown, the value of this embodiment is 2.9.

[0053] The composite material prepared in this comparative example does not contain ammonia water, so that lignin cannot form a composite structure with MXene. The lignin particles are unevenly distributed on the surface of the flaky MXene and are easy to agglomerate, and the ultraviolet shielding ability is weak.

[0054] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a MXene / lignin two-dimensional nanosheet composite material, characterized in that: Step (1) dispersing lignin and deionized water by ultrasonication, and freeze-drying the obtained dispersion in a vacuum to obtain flaky lignin; Step (2) dissolving lithium fluoride in a concentrated hydrochloric acid solution to obtain a lithium fluoride hydrochloric acid mixed solution, then gradually adding Ti3AlC2MAX powder to the mixed solution, reacting at 25-50°C; centrifuging, washing, and freeze-drying to obtain MXene; Step (3) dispersing the flaky lignin obtained in step (1) into the MXene obtained in step (2), adding the mixture into ammonia water, stirring the mixture at room temperature for a period of time, ball milling, obtaining a MXene / lignin nanosheet mixed solution, and freeze-drying the precipitate obtained after centrifugation to obtain a MXene / lignin two-dimensional nanosheet composite material.

2. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The ultrasonic dispersion conditions in step (1) are: ultrasonic dispersion at 225-250 W for 20-30 minutes.

3. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: In step (2), the concentration of the concentrated hydrochloric acid solution is 9-10 M; the concentration of the lithium fluoride hydrochloric acid is 0.02-0.08 g / mL.

4. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: In step (2), the mass ratio of lithium fluoride to Ti3AlC2MAX is 1 to 5:

1.

5. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: In step (2), the reaction time is 24 to 48 hours.

6. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: In step (3), the mass ratio of flaky lignin to MXene is 1:0.5~2.

7. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: In step (3), the concentration of ammonia water is 0.52 M~3.72 M, and the concentration of the MXene / lignin ammonia water mixed solution is 0.045 g / mL~0.27 g / mL.

8. The method for preparing the MXene / lignin two-dimensional nanosheet composite material according to claim 1, characterized in that: The ball milling was performed at a speed of 450-600 rpm for 3-6 h.

9. A MXene / lignin two-dimensional nanosheet composite material prepared according to the method according to any one of claims 1 to 8.

10. Use of the MXene / lignin two-dimensional nanosheet composite material prepared according to the method according to any one of claims 1 to 8 as an ultraviolet shielding agent.

Citation Information

Patent Citations

  • Preparation method of nano lignin particle with uvioresistant effect

    CN108420751A

  • Nanometer lignin carbon-zinc oxidecomposite material as well as preparation method and application thereof

    CN112072085A

  • Preparation method and application of layered hydroxide / dealkalized lignin composite material

    CN118755278A

Cited By

  • Lignin intercalation two-dimensional nano material as well as preparation method and application thereof

    CN120771840A

  • Preparation method and application of MXene-lignin flexible film

    CN121248987A